A pilot study of an integrated mental health, social and medical model for diabetes care in an inner‐city setting: Three Dimensions for Diabetes (3DFD). Issue 10 (7th May 2019) - Ismail, K.; Stewart, K.; Ridge, K.; Britneff, E.; Freudenthal, R.; Stahl, D.; McCrone, P.; Gayle, C.; Doherty, A. M.
Abstract: Aims: We examined the effectiveness of a service innovation, Three Dimensions for Diabetes (3DFD), that consisted of a referral to an integrated mental health, social care and diabetes treatment model, compared with usual care in improving biomedical and health economic outcomes. Methods: Using a non‐randomized control design, the 3DFD model was offered in two inner‐city boroughs in London, UK, where diabetes health professionals could refer adult residents with diabetes, suboptimal glycaemic control [HbA1c ≥ 75 mmol/mol (≥ 9.0%)] and mental health and/or social problems. In the usual care group, there was no referral pathway and anonymized data on individuals with HbA1c ≥ 75 mmol/mol (≥ 9.0%) were collected from primary care records. Change in HbA1c from baseline to 12 months was the primary outcome, and change in healthcare costs and biomedical variables were secondary outcomes. Results: 3DFD participants had worse glycaemic control and higher healthcare costs than control participants at baseline. 3DFD participants had greater improvement in glycaemic control compared with control participants [−14 mmol/mol (−1.3%) vs. −6 mmol/mol (−0.6%) respectively, P < 0.001], adjusted for confounding. Total follow‐up healthcare costs remained higher in the 3DFD group compared with the control group (mean difference £1715, 95% confidence intervals 591 to 2811), adjusted for confounding. The incremental cost‐effectiveness ratio was £398 per mmol/mol unit decrease in HbA1c, indicating the 3DFD intervention was more effective and costed more than usual care. Conclusions: A biomedical, psychological and social criteria‐based referral system for identifying and managing high‐cost and high‐risk individuals with poor glycaemic control can lead to improved health in all three dimensions. What's new?: There are few evidence‐based models of diabetes care that include mental health and social care. The Three Dimensions for Diabetes (3DFD) model integrated social care, mental health and diabetes care into one service. This non‐randomized, observational study, set in three diverse boroughs in London, UK, recruited adults with suboptimal glycaemic control and mental health and/or social problems. 3DFD was associated with clinically significant reductions in glycaemic control but because they were already a very expensive and high‐risk group, there was no evidence of reduction in costs compared with the control group.